PENERAPAN PERANGKAT PEMBELAJARAN IPA DENGAN PENDEKATAN SCIENTIFIC PADA POKOK BAHASAN PENCEMARAN LINGKUNGAN UNTUK MELATIHKAN THINKING SKILLS SISWA MI DI LAMONGAN - Ummu Khairiyah; Mudzaki Risma; Muhammad Sigit Prasetyo (Universitas Islam Lamongan, 2019)
This study aims to determine students' thinking skills (critical thinking skills) after using learning tools with a scientific approach. This study was carried out on 12 students SDN Tenggerejo 2 Kedungpring Lamongan. technique of collecting data by providing pretest and posttest questions. This study usesthe design of the one group pretest posttest. The results show that there is an increase in students' critical thinking skills after learning with a scientific approach